Recompondo a composição: narrativa (auto)biográfica sobre metodologias utilizadas nas aulas de composição oferecidas na banda de música da ala 4 - Silva, Dimas Artur da (2022)
Linked to the Education and Arts research line and to the NarraMus research group, this study investigated the composition and arrangement process with the participants of the musical composition and arrangement study group offered to the military members of the music band at the Santa Maria, based and guided by the perceptions and thoughts of Nachmanovitch (1993), about the development of these observations. In the meantime, departing from the view of conservative music teaching, Vasconcelos (2002) and from the master-apprentice relationship, Louro (2004) and Gaunt (2008). The class diaries and the reflective diaries as well as the questionnaires were used in the acquisition of the data that fed her. From this, a study group on composition and arrangement was formed, lasting five months. The study group, under a new pedagogical-musical perspective, used the cultural-musical experience of the participants as a driving force in the acquisition of compositional and arrangement knowledge. In the classes, audio and video recordings of musical works from the participants' experience were used, as well as other audios and videos of examples of popular and erudite works, in order to support compositional and arrangement ideas. The study of the data obtained in the group took place in a qualitative way and considered two basic conditions for analysis: creativity and creative barriers. Regarding the expected results of the work and the contributions to the teaching of musical composition at the higher level, it is inferred that the pedagogical perspective was presented as a positive plan and an opportune tool for the epistemology of musical composition. The process of musical creation and arrangement worked on in the study group culminated in musical compositions and arrangements made by the participants, leading them to star in their own musical stories based on experiences. The general objective of the work was to investigate the pedagogical dilemmas of the composition teacher and the questions of the students participating in the study group. The specific objectives sought to punctuate the students' questions regarding compositional theories from their experiences, locate the composition teacher's dilemmas in the same process and point out the presence of students' cultural background in the compositions and arrangements developed. The research intends to contribute to the debates of Music Education, regarding a possible expansion of the tradition of conservatories, through the use of the students' baggage.